Sexual Harassment and Assault in Domestic Work: An Exploration of Domestic Workers and Union Organizers in Brazil. - Ribeiro Corossacz, Valeria (Journal of Latin American & Caribbean Anthropology, 2019)
The literature has shown that sexual harassment and assault of domestic workers in the workplace is a problem globally. It is widespread in Brazil, where it is closely linked to the country's slave‐owning past. This article uses interviews with domestic workers and union organizers to investigate this issue in relation to the conditions that characterize domestic work and the racism and sexism in Brazilian society. The analysis focuses on women's reactions to sexual assault and the silence surrounding it. I argue that women's silence in relation to their experiences of sexual assault should be interpreted as a form of agency and resilience within a broader context of social oppression. [Brazil, class, gender, labor, race, social anthropology]